Efektifitas Penggunaan Dental Story E-Book terhadap Peningkatan Pengetahuan tentang Karies pada Anak Sekolah Dasar - Widodo, Yufen; Ismalayani, Ismalayani; Hanum, Nur Adiba (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Palembang, 2024)
Background: Dental caries is a disease that destroys tooth tissues, starting from the enamel, then the dentin, until it reaches the pulp. Increased knowledge can shape better and healthier behaviors. One way to increase knowledge is through education, especially using digital technology that is popular among children. Dental story e-book is a digital storybook containing text, images, and colors, which can be read through electronic devices. The purpose of this study was to determine the effectiveness of using Dental Story E-Books in increasing knowledge about dental caries in elementary school children. Methods: A quasi-experimental design with a pretest-posttest and control group was used. The questionnaire used has been tested for validity and reliability. The research sample consisted of 40 fifth-grade students at SDN 115 Palembang, selected through purposive sampling. A paired t-test was used. Results: The paired t-test resulted in a p-value of 0.001 (p<0.05), indicating that the use of Dental Story e-books was significantly effective in increasing knowledge about dental caries in elementary school children. Conclusion: The use of Dental Story E-Books is effective in increasing knowledge about dental caries in elementary school children.